Results of Nucleos(t)ide Analog Treatment Discontinuation in Hepatitis B e-Antigen-Negative Chronic Hepatitis B: NUCSTOP Study - Kiremitçi, Sercan; Koçhan, Koray; Seven, Gülseren; Biberci Keskin, Elmas; Okay, Gülay; Akkoyunlu, Yasemin; Koç, Meliha Meriç; Sümbül, Bilge; Şentürk, Hakan (Turkish Journal of Gastroenterology, 2024)
Background/Aims: This study aims to investigate the effects of nucleos(t)ide analogs (NAs) discontinuation in eligible patients in accor dance with the Asian Pacific Association for the Study of the Liver hepatitis B guideline and the factors affecting clinical and virological relapses. Materials and Methods: In this prospectively designed study, hepatitis B e antigen (HBeAg)-negative chronic hepatitis B patients who were followed up between 2012 and 2019 were evaluated and 57 patients were included. All participants enrolled the study were HBeAg negative status at NA initiation. Results: The median age of the patients was 49 (29-72) years and 24 (42%) were females. The median treatment duration was 96 (36 276) months and patients were followed for a median duration of 27 months. Sixteen patients had a previous history of NA switch, and thirteen of these patients had a history of lamivudine resistance. Thirty-eight of 57 patients (66%) developed an elevated hepatitis B virus deoxyribonucleic acid level of >2000 IU/mL at least once, defined as virological relapse and 23 (60%) of them, experienced clinical relapse. Thirty-one of 57 patients were re-treated during the follow-up, and hepatitis B surface antigen (HBsAg) loss occurred among 4 (7%) patients. All patients who experienced HBsAg loss had a history of lamivudine resistance (P = .002). Conclusion: Despite receiving NAs suppression therapy for a long time, HBsAg loss occurs rarely. Although it was not life-threatening, most patients experienced relapses and treatment should be restarted. In our study, whether it is a coincidence that all patients with HBsAg loss are patients in whom NAs are used sequentially due to lamivudine resistance is an issue that needs to be further investigated. Cite this article as: Kiremitçi S, Koçhan K, Seven G, et al. Results of nucleos(t)ide analog treatment discontinuation in hepatitis B e-antigen-negative chronic hepatitis B: NUCSTOP study. Turk J Gastroenterol. 2024;35(1):17-26.